Uncommon Presentation of Hip Pain Due to Calcific Tendonitis in the Rectus Femoris - Rayavarapu Hari Krishna; Vijay Kumar Jain; Swaminathan Ramasubramanian; Naveen Jeyaraman; Madhan Jeyaraman (Journal of Orthopaedic Case Reports)
Introduction: Calcific tendonitis is characterized by calcium hydroxyapatite crystal deposition in tendons, leading to inflammation and pain. While predominantly observed in the rotator cuff tendons of the shoulder, its occurrence in the rectus femoris tendon of the hip is exceedingly rare and poses a diagnostic challenge. Case Report: A 38-year-old female housewife presented with a 1-month history of left hip pain, which was dull, aching, and exacerbated by movements such as standing and walking. High-resolution computed tomography imaging showed calcification at the insertion of the left rectus femoris muscle. A magnetic resonance imaging confirmed the diagnosis, revealing no significant abnormalities in the hip joints or surrounding structures. The patient was diagnosed with calcific tendonitis at the insertion of the left rectus femoris muscle and was managed conservatively with rest, Non-steroidal anti-inflammatory drugs, and physical therapy. Follow-up visits were scheduled to monitor her progress and response to treatment. Conclusion: This case underscores the importance of thorough clinical and imaging evaluations in diagnosing calcific tendonitis in atypical locations. Conservative treatment proved effective, highlighting the need for tailored management strategies. Future research should focus on elucidating the pathogenesis and optimizing treatment for calcific tendonitis in uncommon sites.